182 Flow Characteristics Enhanced by the Compliant Arteries and their effects in Vulnerable Plaque Formation. (6th June 2015) - Pereira, Glaucia da Conceicao; Krams, Rob
Abstract : Introduction: According to the literature, the annual deaths caused by cardiovascular diseases are dramatically increasing. 1, 2 In addition to the human costs, in the UK alone, the annual cost related to the treatment of cardiovascular diseases peaked at £6.8bn in 2013. Research on the effects of the mechanical forces sensed by the endothelial cells on plaque morphology and the transport of species into the arterial wall contributed to the understanding of some mechanisms that drive plaque build up. 3, 4 In former works, we suggested that blood particles as the erythrocytes might affect the distribution of the stresses, which might affect homeostasis at locations affected by atheroma formation. 5, 6 In this work, we assess the effects of the wall compliance in mechanical forces directly related to inflammatory signalling pathways, at locations that are recognised as predilection sites for plaque deposition. Methodology: The interaction between blood and the artery is simulated using a three-step coupling method, 7 resolving the equations of motion of the solid (arterial wall) and the fluid (blood) domain separately. Forces resulting from fluid-wall interactions are considered to be elastic and based on Hooke's law (elastic wall model). The plasma is modelled as a Newtonian incompressible fluid using the Navier-Stokes equations. Results: Simulations of a fluid-structure interaction (FSI) model that mimic the coupling blood-artery have yielded results comparable with the literature. 8 To assess the differences in flow due to both geometrical and physiological variations, we applied the model to the simulation of blood flow in arterial segments acquired by 3D-reconstruction of the cardiovascular system of two species: mouse and pig. The flow recirculation and differences in the velocity distribution were enhanced by the wall compliance. The variations in the flow characteristics are more prominent at predilection sites for plaque deposition. Conclusions: Our results suggest that changes in flow due to the arterial compliance are important at predilection sites for plaque deposition, in different species. Therefore, at sites of increasing cellular activity due to inflammation (vulnerable plaques) computational models of blood flow related to atheroma formation might account for the effects of the arterial movement. References: Mendis S et al . World Health Organization and the World Heart Federation and the World Stroke Organization Report, 2011 Camacho H, Günther D, von Banchet B, Zimmer B. J Physiol . 2005;564 :683–96. Fang D, Wood O, Lawson B. J Physiol . 2003:1 ;550:739–52. Frzel B, Waxman D-H. Mol Pain . 2012;8 :82. Pereira G et al, The British Atherosclerosis Society Meeting. 2014. Pereira G et al . The Medical Engineering Centres Annual Meeting and Bioengineering. 2014;4. Abaqus http://abaqus.cc.ic.ac.uk/v6.12/index.html . Janela J et al . Mec. Computational. 2010.